Experimental research on KDP crystal slicing with resin bonded diamond abrasive wire saw. Issue 5 (November 2016) - Ge, Mengran; Bi, Wenbo; Ge, Peiqi; Bi, Yuchao
Abstract KDP (KH2 PO4 ) crystals is a kind of excellent nonlinear optical crystals, which has been widely used in nonlinear optical and inertial confinement fusion (ICF) engineering. Slicing processing is the first machining process of KDP crystal's optoelectronic component, which has an important influence on the yield rate of KDP crystal chip. This paper presents the experimental research on KDP crystal slicing with reciprocating wire saw machine tool and resin bonded diamond wire saw. For the slicing surface roughness and surface morphology of KDP crystals as evaluation index, three factors and three levels of orthogonal tests are designed. The factors are workpiece feed rate, wire saw tension force, and wire saw moving speed. The slicing surface morphology is observed by SU-70 hot field emission scanning electron microscopy (SEM), and the surface roughness is measured with the TR240 portable surface roughness meter. Through the analysis of the experimental results, the optimized slicing parameter combination is obtained, and the optimal process parameters are verified by slicing experiments. The results show that the workpiece feed rate is the main influence factor on slicing surface quality of KDP crystals.